Internal and External Factors of Putin’s War on Ukraine - Mara Morini (De Europa)
In literature it has been widely debated that domestic politics and international relations are often somehow entangled to the extent that it is quite difficult “whether domestic politics really determines international relations, or the reverse” (Putnam 1988:423). In this respect, the study of the Russian invasion in Ukraine can offer an opportunity to better understand the relationship between domestic and external factors that have determined Vladimir Putin’s choice to attack the Ukrainian territory. So far, studies have interpreted “Putin’war” as a nostalgic choice based on the will to restore former imperial glories to unify the Russian peoples denying, at the same time, the Ukranians’ right to live in an independent State (Kuzio 2022; Zaporozhchenko 2024). Other scholars argued that the Russian invasion was mainly the effect to the Western policies – especially the NATO enlargement – perceived as a security threat by the Kremlin (Maersheimer 2014). What it is still missing in literature is an analysis, which combine the main domestic reasons - i.e. Putin’s personality and ideology, the institutional design, the legacies of the historical and cultural traditions – as well as the role played by the external factors (NATO, EU, the US) in determining Russia’s reaction against Ukraine. Consequently, this article aims at describing the main reasons why Putin decided to attack Ukraine and challenge the West trying to analyze both the domestic situation and the international environment, which constitutes the political background of the Russian war. Such an approach will allow a wider overview of the multiple factors – domestic and international –, which provoked the war bearing in mind that some of the findings in this study should be seen as suggestive rather than conclusive.